The Application of Dry-Air Blast to the Manufacture of Iron - JAMES QATLEY (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
THE atmosphere, which plays such an important part in the manufacture of iron and steel, is the most variable element involved in its several processes; and particularly is this true of the blast-furnace process, which consumes air in large quantities. At no time since the blast-furnace became an important and widely used apparatus-even when it was operated in the most crude manner-have the variations in composition of the raw materials used been as frequent and as great as the variations in humility of the atmosphere. Important, improvements have been made in the blast furnace and its accessories, such as the hot-blast stoves, the increase in size and change in the shape of the furnace, more efficient blowing engines, the increased protection given to the bosh walls, and the careful preparation of' the raw material, all of which have exerted a pronounced influence on the furnace-operations from a metallurgical standpoint. But during the past eight years little advance has been made in this direction; the fuel-consumption has not diminished, nor has there been any material increase in production. Within that period, however, there has been witnessed the greatest development in appliances for the economical handling of material. So complete has been the work in this direction, that, except in isolated cases, in this country at least., a further extension does not hold out much promise of a satisfactory return on the investment required. It seemed that, with the exception of the gas-engine, we had about reached the limit, for like a strong wall, the atmosphere, with its humility as variable to-clay as when first blown into a primitive blast-furnace, appeared to stand as a Barrier to